Soil Physical Quality Indices Across Various Land-Use Systems in Giripurno Village, Kota Batu - Rida Yeni Pembayun; Purwadi Purwadi; Fitri Wijayanti (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: Continuous land use and soil cultivation without proper management can affect soil productivity and physical properties. The quality of soil physical properties plays a crucial role in agricultural development. Soil physical properties are key factors supporting crop production because they influence the availability of water and plant nutrients; therefore, it is essential to understand their quality. This study aims to determine and evaluate the quality of soil physical properties on mixed-use farmland, dry fields, and paddy fields in Giripurno Village. Methodology: This study was conducted using a survey method, and soil sampling was performed using purposive sampling, resulting in 12 sample points. Soil samples were collected using a soil sampling ring at soil depths of 0–30 cm and 30–60 cm for each land-use type. The observed soil physical parameters were soil texture, bulk density, permeability, particle density, porosity, and aggregate stability. Data analysis was performed using Excel 2013, and the soil physical property quality index was calculated based on criteria specific to each land-use type. Findings: The results of the study showed that the best soil physical property quality index value was found in mixed gardens at 0.84 with a “good” rating, while the worst was found in rice fields at 0.36 with a “bad” rating. The higher the soil physical quality index, the better the soil quality of a given plot of land. Land use that involves proper, non-excessive cultivation will help maintain soil quality. Contributions: The findings provide a practical basis for sustainable soil management by identifying land-use systems with better physical soil conditions and highlighting the need to improve degraded paddy field soils